2021
DOI: 10.1177/20503121211024462
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B surface antigen and associated factors among mothers who had antenatal care contact in Attat Hospital, southern Ethiopia

Abstract: Introduction: Hepatitis B virus is a viral infection which can cause both acute and chronic liver disease. Predominately, this virus transmitted through the mother-to-child route. It is an endemic disease in low-resource setting countries like Ethiopia. Objective: Therefore, this study was used to assess magnitude and associated factors of hepatitis B surface antigen among pregnant mothers, who had antenatal care in Attat Hospital. Method: The cross-sectional study was conducted from 1 September 2019 to 30 Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…On the other hand, the highest rate of parallel infections was found in this study. The prevalence of HBV was 9% which was in agreement with 10.9% [26] and 7.2% [27] in Southern Ethiopia, 8% in Mali [28] and 6.78% in Nigeria [29] but also higher than previous Ethiopian reports of 3.5% [30] and 6.0% [31]. According to the global magnitude of HBsAg, the present finding is clustered as high ( 8%).…”
Section: Plos Onesupporting
confidence: 89%
“…On the other hand, the highest rate of parallel infections was found in this study. The prevalence of HBV was 9% which was in agreement with 10.9% [26] and 7.2% [27] in Southern Ethiopia, 8% in Mali [28] and 6.78% in Nigeria [29] but also higher than previous Ethiopian reports of 3.5% [30] and 6.0% [31]. According to the global magnitude of HBsAg, the present finding is clustered as high ( 8%).…”
Section: Plos Onesupporting
confidence: 89%
“…This report also indicated that the pooled prevalence of HBV among Nigerian pregnant women was found to be 14.1% [ 35 ]. Other studies which were conducted in Southern Ethiopia (10.9%) [ 36 ], Uganda (11.8%) [ 37 ], Cameroon (10.78%) [ 25 ], and the republic of South Sudan (11%) [ 38 ] showed slightly higher HBV infection rates. This variation in the seroprevalence of HBV among pregnant women might be due to differences in a study period, sample size, demographic characteristics, and other clinical conditions of the study participants across various localities.…”
Section: Discussionmentioning
confidence: 99%